Review of Méliès to 3D: the Cinema Machine exhibition at the Cinémathèque de Paris (October 5th-January 29th, 2017) - David Lipson (Transatlantica)
The exhibition delves into the history and evolution of cinema, shown through the lens of the machines and technology that made the filmmaking process possible. It reveals how technological progress brought about new forms, and conversely, how esthetic pursuit—the desire to see new images—gave birth to new devices and techniques. http://www.cinematheque.fr/cycle/de-Méliès-a-la-3d-la-machine-cinema-356.html.